2012
DOI: 10.1007/s11692-012-9210-7
|View full text |Cite
|
Sign up to set email alerts
|

The Developmental Basis of Quantitative Craniofacial Variation in Humans and Mice

Abstract: The human skull is a complex and highly integrated structure that has long held the fascination of anthropologists and evolutionary biologists. Recent studies of the genetics of craniofacial variation reveal a very complex and multifactorial picture. These findings contrast with older ideas that posit much simpler developmental bases for variation in cranial morphology such as the growth of the brain or the growth of the chondrocranium relative to the dermatocranium. Such processes have been shown to have majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 58 publications
1
45
0
1
Order By: Relevance
“…This is in agreement with some of the previous experiments on other organisms that also failed to find higher levels of FA in phenotypic traits under conditions of nutritional stress (Stige et al, 2004; Vishalakshi and Singh, 2007; Vijendravarma et al, 2011). Although findings in animal models have to be taken with caution because they are difficult to extrapolate to other species, similarities in developmental structure between human and rodent skulls (Martinez-Abadias et al, 2012) validate the inferences made from this study regarding the effect of environmental factors on fluctuating asymmetry in human populations. Overall, the results obtained here from a controlled experiment do not support the view of fluctuating asymmetry of cranial structures as a reliable index for inferring stress in past human populations.…”
Section: Discussionsupporting
confidence: 75%
“…This is in agreement with some of the previous experiments on other organisms that also failed to find higher levels of FA in phenotypic traits under conditions of nutritional stress (Stige et al, 2004; Vishalakshi and Singh, 2007; Vijendravarma et al, 2011). Although findings in animal models have to be taken with caution because they are difficult to extrapolate to other species, similarities in developmental structure between human and rodent skulls (Martinez-Abadias et al, 2012) validate the inferences made from this study regarding the effect of environmental factors on fluctuating asymmetry in human populations. Overall, the results obtained here from a controlled experiment do not support the view of fluctuating asymmetry of cranial structures as a reliable index for inferring stress in past human populations.…”
Section: Discussionsupporting
confidence: 75%
“…We find a large number of both positive and negative correlations among traits, attesting to highly structured patterns of variation. For craniofacial morphology more generally, somatic growth, chondrocranial growth, and brain growth are known to drive such patterns of integrated variation in both mouse and human crania (Cooper et al 2004;Hallgrímsson et al 2006Hallgrímsson et al , 2009Marcucio et al 2011;Martínez-Abadías et al 2012). Here, both facial size and facial shape allometry exhibit a pattern of genetic correlations with facial measures that capture aspects of facial height, midfacial width, and lower facial prognathism.…”
Section: Discussionmentioning
confidence: 99%
“…Given the evolutionary importance of encephalization across vertebrates, it is likely that the developmental pathways that structure the interaction between the developing brain and skull are similar across mammals (Hallgrímsson et al, 2004; Hallgrímsson & Lieberman, 2008; Hallgrímsson, Lieberman, Liu, Ford-Hutchinson, & Jirik, 2007; Martínez-Abadías, Mitteroecker, et al, 2012). The specific genetic variants that initiated phenotypic change during human evolution may differ from a mutation present in a mouse model, but their participation in conserved developmental pathways ultimately will produce similar phenotypic outcomes valuable for our understanding of evolution.…”
Section: Beyond the Fossil Record: Animal Modelsmentioning
confidence: 99%
“…The specific genetic variants that initiated phenotypic change during human evolution may differ from a mutation present in a mouse model, but their participation in conserved developmental pathways ultimately will produce similar phenotypic outcomes valuable for our understanding of evolution. For example, a study comparing cranial morphology with respect to changes in brain size, chondrocranial length, and overall cranial size concluded that the structure of cranial variation as a result of these factors was similar in both mice and humans, pointing to similar developmental processes (Martínez-Abadías, Mitteroecker, et al, 2012). Additionally, carefully annotated data pertaining to similarities in the neurodevelopmental sequence of events and patterns of brain enlargement across mammalian orders reveal a high degree of conservation (Clancy, Darlington, & Finlay, 2001; Finlay & Darlington, 1995; Workman, Charvet, Clancy, Darlington, & Finlay, 2013), providing further support for the use of mouse models in the study of human encephalization.…”
Section: Beyond the Fossil Record: Animal Modelsmentioning
confidence: 99%